GENDER STEREOTYPES: PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF THE DEVELOPMENT OF SOCIAL THINKING IN ADOLESCENTS (Universal International Scientific Journal, 2026)
This article analyzes the impact of gender stereotypes on the development of social thinking in adolescents from a pedagogical and psychological perspective. The article comprehensively covers the theoretical foundations of gender stereotypes, their manifestations in adolescents, and their negative impact on social decision-making processes. The role of the main socialization institutions such as family, school, and media in the formation of gender stereotypes, as well as pedagogical approaches to the development of critical thinking in combating them, is examined. Based on the results of empirical research, the article provides practical recommendations for educational practice and identifies urgent tasks for ensuring gender equality in society.
Keywords: Gender stereotypes; teenagers; social thinking